Dignity and respect: important in volunteer settings too!. Issue 3 (20th March 2015) - Paull, Megan; Omari, Maryam
Abstract : Purpose: – Volunteers in some organisations are subject to new protections under legislative amendments in Australia which proscribe workplace bullying. These new protections provide impetus for the question of whether workplace bullying is an issue for (unpaid) volunteers and (paid or unpaid) volunteer managers. The purpose of this paper is to outline key exploratory findings. Design/methodology/approach: – This exploratory and descriptive qualitative study employed an online survey to collect data on the experiences of participants and on their perception of what constitutes bullying in volunteering. Findings: – The evidence suggests that many of the negative behaviours which might be found in workplaces are also found in volunteering, but there are also aspects unique to this setting. Research limitations/implications: – This study was exploratory in nature and will benefit from further expansion and empirical testing. Practical implications: – Many respondents reported that they have been subject to, or witnessed events which they considered to be bullying. Recognition of the possibility of bullying in volunteering is a step towards amelioration. Social implications: – Volunteering has benefits for individuals and organisations, as well as contributing to social capital. Organisations which are cognisant of, and actively build positive cultures are better able to attract and retain talented and committed volunteers and managers. Originality/value: – There is an absence of research relating to workplace bullying in volunteer settings. As context plays a significant role in workplace bullying scenarios, this study opens up a unique perspective to this negative behaviour in a new setting.